Concerted functions of Streptococcus gordonii surface proteins PadA and Hsa mediate activation of human platelets and interactions with extracellular matrix. (11th October 2016) - Haworth, Jennifer A.; Jenkinson, Howard F.; Petersen, Helen J.; Back, Catherine R.; Brittan, Jane L.; Kerrigan, Steve W.; Nobbs, Angela H.
Summary: A range of Streptococcus bacteria are able to interact with blood platelets to form a thrombus (clot). Streptococcus gordonii is ubiquitous within the human oral cavity and amongst the common pathogens isolated from subjects with infective endocarditis. Two cell surface proteins, Hsa and Platelet adherence protein A (PadA), in S. gordonii mediate adherence and activation of platelets. In this study, we demonstrate that PadA binds activated platelets and that an NGR (Asparagine‐Glycine‐Arginine) motif within a 657 amino acid residue N‐terminal fragment of PadA is responsible for this, together with two other integrin‐like recognition motifs RGT and AGD. PadA also acts in concert with Hsa to mediate binding of S. gordonii to cellular fibronectin and vitronectin, and to promote formation of biofilms. Evidence is presented that PadA and Hsa are each reliant on the other's active presentation on the bacterial cell surface, suggesting cooperativity in functions impacting both colonization and pathogenesis.